Polyphenol Composition of Extracts of the Fruits of Laserpitium Krapffii Crantz and Their Antioxidant and Cytotoxic Activity - Anna Bogucka-Kocka; Natalia Vorobets; Małgorzata Chrząszcz; Wioleta Pietrzak; Katarzyna Szewczyk (Antioxidants, 2019)
During inflammation, reactive oxygen species (ROS) are produced in large amounts, causing oxidative stress. Several studies confirm that plant extracts rich in phenolic compounds may inhibit ROS production. For that reason, the aim of this work is the qualitative and quantitative analysis of phenolic acids and flavonoids in the etheric (LAEN) and methanolic (LAM) extracts of the fruits of Laserpitium krapffii Crantz, as well as their antioxidative and cytotoxic properties. Liquid chromatography−electrospray tandem mass spectroscopy (LC-ESI-MS/MS) enabled the identification of 12 phenolic acids and nine flavonoids. Both tested extracts scavenged ROS in a concentration-dependent manner. Stronger activity was observed for the methanolic extract. The cytotoxic effect of both extracts in increasing concentrations on five types of cancer cell lines was also investigated. The cytotoxicity was estimated using trypan blue vital staining. It was found that the analyzed extracts induced the apoptosis of the cells of all the tested cell lines. In conclusion, our results present that the fruits of L. krapffii can be a source of valuable compounds with protective effects against oxidative damage.